Association of vision impairment with suicide ideation, plans, and attempts among adults in the United States. Issue 11 (26th August 2022) - Lee, Othelia E.‐K.; Park, Daejun; Park, Junghyun
Abstract: Objective: This study aims to investigate the relative strength of association between vision impairment (VI) and suicidal ideation, plans, and attempts among adults in the United States. Method: The study sample consisted of 214, 505 adults, aged 18 years and older. Researchers used data from the 2015–2019 National Survey on Drug Use and Health, in which respondents were asked whether they had any suicidal thoughts, plans, and attempts, in the past 12 months. Results: Approximately, 4.4% of respondents reported experiencing VI, being blind, or having serious difficulty seeing. Compared to their sighted peers, a relatively high proportion of adults with VI had serious thoughts about suicide (9.0%), suicidal plans (3.0%), or suicidal attempts (1.6%) in the past year. The findings showed that individuals with VI may disproportionately experience suicidal ideation, plans, and attempts, after controlling potentially confounding variables (adjusted odds ratio [AOR] = 1.36; AOR = 1.27; AOR = 1.40, respectively). Conclusion: With findings demonstrating such a strong association between VI and suicide, this study suggests the importance of screening for suicidal ideation, plans, and attempts among adults with VI, and the strong need for developing behavioral health services which keep this correlation in mind.